Factors influencing intent to receive COVID-19 vaccination among Black and White adults in the southeastern United States, October - December 2020 - Jennifer Cunningham-Erves; Carol S. Mayer; Xijing Han; Landon Fike; Chang Yu; Phyllis M. Tousey; David G. Schlundt; Deepak K. Gupta; Michael T. Mumma; David Walkley; Mark D. Steinwandel; Kathryn M. Edwards; et al. (Taylor & Francis Group, 2021)
Vaccination intent is foundational for effective COVID-19 vaccine campaigns. To understand factors and attitudes influencing COVID-19 vaccination intent in Black and White adults in the US south, we conducted a mixed-methods cross-sectional survey of 4512 adults enrolled in the Southern Community Cohort Study (SCCS), an ongoing study of racial and economic health disparities. Vaccination intent was measured as "If a vaccine to prevent COVID-19 became available to you, how likely are you to choose to get the COVID-19 vaccination?" with options of "very unlikely," "somewhat unlikely," "neither unlikely nor likely," "somewhat likely," and "very likely." Reasons for intent, socio-demographic factors, preventive behaviors, and other factors were collected. 46% of participants had uncertain or low intent. Lower intent was associated with female gender, younger age, Black race, more spiritual/religious, lower perceived COVID-19 susceptibility, living in a greater deprivation area, lower reading ability, and lack of confidence in childhood vaccine safety or COVID-19 vaccine effectiveness or safety (p < .05 for all). Most factors were present in all racial/gender groups. Contextual influences, vaccine/vaccination specific issues, and personal/group influences were identified as reasons for low intent. Reasons for higher intent included preventing serious illness, life returning to normal, and recommendation of trusted messengers. Hesitancy was complex, suggesting tailored interventions may be required to address low intent.